Diversity in Hydrogen-rich Envelope Mass of Type II Supernovae. II. SN 2023ixf as Explosion of Partially Stripped Intermediate Massive Star - Fang, Qiliang (2024)
SN 2023ixf is one of the most well-observed core-collapse supernovae in recent decades, yet there is inconsistencyin the inferred zero-age main-sequence (ZAMS) mass MZAMS of its progenitor. Direct observations of the pre-supernova (SN) red supergiant (RSG) estimate MZAMS spanning widely from 11 to 18 Me. Additional constraints,including the host environment and the pulsation of its progenitor RSG, suggest a massive progenitor withMZAMS > 17 Me. However, the analysis of the SN properties, from light-curve modeling to late-phasespectroscopy, favors a relatively low-mass scenario (MZAMS < 15 Me). In this work, we conduct a systematicanalysis of SN 2023ixf, from the RSG progenitor, plateau phase light curve to late-phase spectroscopy. UsingMESA+STELLA to simulate the RSG progenitor and their explosions, we find that a range of the RSG modelshaving MZAMS that vary from 12 to 17.5 Me can reproduce its multiband light curves if the hydrogen-rich envelopemass and the explosion energy are allowed to vary. Using late-phase spectroscopy as an independent measurement,the oxygen line [O I] indicates an intermediate-massive progenitor (MZAMS ∼ 16.0 Me). By incorporating thevelocity structure derived from the light-curve modeling into an axisymmetric model, we generated [O I] lineprofiles that are consistent with the [O I] line observed in late-phase spectroscopy of SN 2023ixf. Bringing theseanalyses together, we conclude that SN 2023ixf is the aspherical explosion of an intermediate-massive star(MZAMS = 15–16 Me), with the hydrogen envelope being stripped to 4–5 Me prior to its explosion.